Effects of mixed provider payment systems and aligned cost sharing practices on expenditure growth management, efficiency, and equity: a structured review of the literature - Isabelle Feldhaus; Inke Mathauer (BMC, 2018)
Abstract Background Strategic purchasing of health care services has become a key policy measure on the path to achieving universal health coverage. National provider payment systems for health services are typically characterized by mixes of provider payment methods with each method associated with distinct incentives for provider behaviours. Reaching incentive alignment across methods is critical to enhancing the effectiveness of strategic purchasing. Methods A structured literature review was conducted to synthesize the evidence on how purposively aligned mixed provider payment systems affect health expenditure growth management, efficiency, and equity in access to services with a particular focus on coordinated and/or integrated care management. Results The majority of the 37 reviewed articles focused on high-income countries with 74% from the US. Four categories of payment mixes were examined in this review: blended payment, bundled payment, cost-containment reward models, and aligned cost sharing mechanisms. Blended payment models generally reported moderate to no substantive reductions in expenditure growth, but increases in health system efficiency. Bundled payment schemes consistently report increases in efficiency and corresponding cost savings. Cost-containment rewards generated cost savings that can contribute to effective management of health expenditure growth. Evidence on aligned cost-sharing is scarce. Conclusion There is lacking evidence on when and how mixed provider payment systems and cost sharing practices align towards achieving goals. A guiding framework for how to study and evaluate mixed provider payment systems across contexts is warranted. Future research should consider a conceptual framework explicitly acknowledging the complex nature of mixed provider payment systems.